Indoor relative humidity as a fire risk indicator. (January 2017) - Log, Torgrim
Abstract: A low cost weather station has been tested for monitoring relative humidity (RH) in sitting rooms as a dry wood fast fire development risk indicator. Ten Norwegian wooden homes/flats, built between 1843 and 2012, were selected for testing during the winter 2015/2016. Linear calibration curves for each in- and outdoor sensor, based on saturated inorganic salt solution controlled air, were needed to ensure ±3% RH accuracy. Recorded average moisture supply to the indoor air during the winter varied from 0.30 to 2.64 g/m 3, with mean 1.29 ± 0.75 g/m 3 . The oldest buildings and the modern balanced ventilation buildings were generally driest. A near step change to drier weather in January resulted in a 6–7 days decay period for recorded indoor RH of the older buildings with wood panel wall linings. This was within reasonable proximity (30%) of theoretically expected step change diffusion controlled wood panel drying. The decay period was shorter for a modern building with plasterboard wall linings. A similarly long decay period was not observed for subsequent rising RH values two weeks later. This discrepancy may be explained by wood desorption adsorption hysteresis. The calibrated weather stations gave reliable results throughout the winter season. They served, and may very well also in the future serve, as detectors for warning local fire brigades about emerging dry wood fire risk situations. Due to hysteresis, more research is, however, needed to know when to call off a dry indoor climate high fire risk condition as the conditions gets less dry. Highlights: Low cost weather station tested as dry wood villa fire risk indicator. Saturated salt solutions gave successful sensor calibration to ±3% RH. Significant moisture buffering documented in 60–100 years old wooden villas. 5–7 days decay period for indoor RH adjustment to dry ambient air. Monitored indoor RH successfully used to warn local fire brigades.